A CONTROLLING MONITORING WATER DEPTH AND TURBIDITY BASED ON INTERNET THING - Hendra Wahyu Niryulianto; Muhammad Fahreza; Muhammad Erpandi (Sean Institute, 2023)
Based on the results of the research conducted, there were problems found that when the process of checking the depth and turbidity of water quality was still using a manual system that involved the role of employees in carrying out the checking process using a opacimeter and level transmitter. Therefore, researchers provide input and suggestions for the process of checking the depth and turbidity of Water using sensors to get the results of checking and an Internet of Things based system to monitor the results of the sensors used.Then the results of the process can be monitored directly into the website platform. In this research, the writer uses fuzzy logic method to program the hardware and monitoring results use a website with codeigneter framework. Which aims to build a monitoring system for checking the depth and turbidity of water quality automatically using ultrasonic sensors and turbidity sensors.